Detection of major mastitis pathogens by multiplex polymerase chain reaction assay in buffalo milk - CHARAYA, GAURAV; SHARMA, ANSHU; KUMAR, ASHOK; GOEL, PARVEEN; SINGH, MAHAVIR (The Indian Journal of Animal Sciences, 2015)
In the present study multiplex PCR assay was standardized for simultaneous detection of Staphylococcus aureus, Streptococcus agalactiae, S. dysgalactiae and Escherichia coli associated with mastitis. The target sequence 16S to 23S rRNA inter spacer regions was used. Primers used were chosen to have approximately same Tm value, common annealing temperature and easily differentiable specific amplified products. The performance of the assay was examined on 92 milk samples collected from subclinically and clinically infected buffaloes and the diagnostic sensitivity and specificity of multiplex PCR was compared with culture examination. Out of total milk samples, 16 were diagnosed for mixed infections of Staphylococcus aureus + S. dysgalactiae (43.75%), S. aureus + S. agalactiae(12.5%), S. aureus + E. coli (25%), S. dysgalactiae + E. coli (12.5%) and S. aureus + S. dysgalactiae + E. coli (6.25%). Multiplex PCR assay was more promising option than culture methods. Milk culture method is cumbersome and more time consuming and it may yield no bacteria due to the presence of very low number of pathogens or due to residual therapeutic antibiotics concentration in milk. The assay has an added advantage over simplex PCR that it can simultaneous detect and type different species of bacteria. Multiplex PCR assay is rapid, sensitive and specific assay which can be used as a routine diagnostic tool to detect major mastitis pathogens.